Optimization of Persuasion Elements in Car Salon Brochure Using Graphic Design Morphology Analysis, Zero-One and Evaluation Matrix - Didik Eko Prasetyo; Fourry Handoko; Julianus Hutabarat (CV. Syntax Corporation Indonesia, 2024)
The development of the advertising world is growing from two dimensions (brochures, pamphlets and fryers), which is currently trending is moving advertisements in the form of animation or video. With these developments, brochures are considered less attractive for use in sales promotion. This research uses a mixed method consisting of two stages. The first stage is the determination of factors or elements of choice using Value Engineering and Analytic Hierarchy Process (AHP), while the second stage is design analysis using typographic analysis in design creation and weight measurement using an evaluation matrix. The research population was experts relevant to the field of study, totaling 45 people. Based on the Slovin formula and AHP, the sample obtained was 31 experts from a population of 45 people. The brochure was then weighted to determine the value through a survey. The results of the survey conducted by analyzing the evaluation matrix, obtained responses from experts have shown a significant increase in the weight value of the redesigned brochure advertisement, so it is concluded that the redesign step with persuasion management and design form can increase the weight of the brochure again.